Analysis of Nutritional Needs In Elementary School-Aged Children In Remote, Underdeveloped, and Border Regions Using Android-Based Artificial Neural Network Method - Febriani, Arisa; Apdillah, Dicky (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2025)
The nutritional needs of elementary school children are very important to support their growth, development, and learning abilities. Good nutrition is essential to support the growth of bones, muscles, and organs. In addition, protein, calcium, and iron intake are very important. Nutrition also affects brain function, including children's concentration and memory. One of the schools where various factors related to children's nutrition can be studied is State Elementary School 134633 Tanjung Balai. It is hoped that the analysis of nutritional needs in school children can provide an overview of food consumption patterns, nutritional status, and the factors that influence them. The system developed using the Artificial Neural Network (ANN) model with the Backpropagation algorithm successfully analyzed the nutritional status of children based on the data provided. By categorizing nutritional status into thin, fat, and normal, the system can provide adequate results for the nutritional analysis needs of Elementary School Children in the 3T Area.